Evaluation of practice teachers according to the views of teacher candidates - Tuncer, Murat (Sila Science, 2012)
Teaching practice course has been included in all teacher education programs with the purpose of providing teacher candidates with a medium to test the knowledge they gained throughout their teaching education in practice. There is great contribution of practice teachers, who provide guidance to teacher candidates, to the delivery of this course in accordance with its purpose and in a successful manner. This research is motivated by this line of thought. Data was collected from a total of 322 teacher candidates having pedagogical formation education in Firat University, Faculty of Education and graduated from Faculty of Humanities and Social Sciences and Faculty of Science and senior students in the Department of Computer and Education Technologies and the Department of Primary School Mathematics Teaching in the Faculty of Education by applying practice teacher's qualification scale. Cronbach's alpha coefficient of the scale is 0.96. Independent samples t test, Anova test, and in case the distribution was not homogeneous Kruskal Wallis H and Mann Whitney U tests were used for the analysis of the data. Moreover, correlation analysis, percentage, and frequency analyses were also conducted. According to the findings obtained, there is a significant difference between genders in terms of teacher candidates' expectations from their practice teachers and qualifications of practice teachers' for satisfying these expectations. It was detected that according to the views of teacher candidates, practice teachers have shortfalls in the areas of guidance, valuing practice, and communication.
Keywords: Teaching practice; Teacher candidates; Practice teacher; Teaching profession